Developing Sustainable Muslim-Friendly Tourism Village Model Through Digital Tourism: Perspective of Shari’ah Economy - Noviarita, Heni; Kurniawan, Muhammad; Normasyhuri, Khavid (Universitas Islam Negeri Raden Intan Lampung, 2024)
Using digital technology and social media is important in advancing sustainable tourism and expanding its appeal internationally. In this regard, the digitalization program for tourist villages needs to be encouraged because it has significant prospects in increasing the number of visitors while supporting the sustainability of tourism. This study aims to discuss the development of a sustainable tourist village model through a digital tourism approach carried out in the Provinces of West Java, the Special Region of Yogyakarta, and Lampung from an Islamic economic perspective. Data were obtained through observation and questionnaire methods from primary and secondary sources. The collected data were then processed and analyzed using triangulation and SWOT techniques. The study results show that the three provinces above have good internet access, making it possible to promote tourism potential through digital platforms. In terms of opportunities, adopting the digital tourism concept can open up great potential in increasing tourist engagement and market expansion. On the other hand, the lack of information and limited Human Resources must be addressed because they can hinder marketing potential and operational effectiveness. In addition, tight competition with other tourist areas must be anticipated because it can reduce investment interest and tourist visits. The sustainable tourism village model development through an environmentally friendly tourism approach has a strong foundation from a shari’ah perspective because it is supported by the Qur’an, Hadith, and the fatwa of the DSN MUI.